AKTIFITAS WANITA SASAK SEBAGAI SUMBER IDE PENCIPTAAN KARYA LUKIS - Zainudin Zainudin; BT. Dewobroto (KalaTanda, 2021)
Sasak women's activities has variousform of traditional works, such as minsah, weaving, betel nut (Mamaq), and so on. The various activities of Sasak women who were so attractive lately began to disappear; creates an urge to devote and appreciate it in paintings. The method of creating this work goes through several stages, including observing, learning, and concentrating ideas related to the theme raised. Exploration uses two forms, namely visual exploration and conceptual exploration. The source of data in the idea of creation is primary data from direct observation. As for the secondary data from books and the internet. The method of analysis is through a reduction process, the data that has been selected is embodied in a visual form with an initial embodiment through simple sketches. Sketching is done on paper media. The results of the sketches that were made were then sorted and eight sketches were selected according to the theme. The result is eight realist paintings entitled: Minsah, Bait aik, Begutu, Meriap, Nyensek, Nampik, Selling cloth, Mamak. Keywords: Sasak women’s activities, Painting, Realism.